Co-inoculation with Yeast and LAB Under Winery Conditions: Modification of the Aromatic Profile of Merlot Wines - Antalick, G.; Perello, M.C.; de Revel, G. (South African Journal of Enology and Viticulture, 2013)
The present work reports the impact of yeast/LAB co-inoculation on the aromatic profile of Merlot wines made in wineries. This study was carried out over two consecutive years on five Merlot wines in Bordeaux and Swiss wineries, using Saccharomyces cerevisiae and Oenococcus oeni starter cultures. Seventy aromatic compounds were quantified and, in addition, the sensory profiles of two wines were determined in order to compare the aromatic notes of the sequential and co-inoculated wines. The influence of the timing of inoculation with lactic acid bacteria (LAB) on the metabolic profile of wines was observed. It confirmed previous work carried out on a micro-scale but, for the first time, the impact of yeast/LAB co-inoculation was significantly demonstrated from a sensory point of view under winery conditions. In particular, the fruity and lactic notes, as well as the markers associated with these descriptors, such as esters and diacetyl, were altered. Co-inoculation does not always favour fruity expression, nor does it reduce the diacetyl content and lactic aroma intensity. All of the trends were observed either in the production and degradation of metabolites, or by the development of an aromatic mask over the short and long term.